Solidarity and Performance Differences - Marion Eberlein; Judith Przemeck (University of Bonn, Bonn Graduate School of Economics (BGSE), 2006)
To investigate the influence of performance differences on donating behavior in a solidarity game we introduce a real effort task. In each three-person-group subjects are ranked according to their task performance. Since each potential winner is informed about his own rank and the potential losers? ranks, they are able to regard performance differences between various potential losers and between themselves and a potential loser. We run another treatment without a real effort task to check for the influence of performance. We find different kinds of donating behaviour which seem to be fundamental characteristics.
Keywords: D31; C91; 330; Solidarity; Performance Differences; Real Effort; Experiment